2011
DOI: 10.1016/j.tube.2011.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A quality assessment tool for tuberculosis control activities in resource limited settings

Abstract: Tuberculosis (TB) is a significant problem, infecting nearly 9 million new patients per year and killing about 2 million a year. The primary means with which to affect TB globally are to decrease transmission locally, mainly by effective identification, diagnosis, and treatment of infectious TB patients. Therefore, quality assurance of TB control efforts at the local level is essential. This study describes the creation of a data extraction tool for retrospective chart review based on the International Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…About one third of the world population is suffering from the infection caused by Mycobacterium tuberculosis [ 1 ]. It was estimated, that in 2012, around 8.6 million people developed TB and approximately 1.3 million people died because of this disease [ 2 ]. The emergence of drug-resistant bacterial strains is one of the main causes for the current spread of TB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…About one third of the world population is suffering from the infection caused by Mycobacterium tuberculosis [ 1 ]. It was estimated, that in 2012, around 8.6 million people developed TB and approximately 1.3 million people died because of this disease [ 2 ]. The emergence of drug-resistant bacterial strains is one of the main causes for the current spread of TB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data quality dimensions, identified using test-based approach, are consistent with terminologies found in existing literature on data quality. However, the approach of collecting or identifying data quality dimensions in TB control programs implemented in other parts of the world is different, e.g., survey [ 7 ], qualitative interview [ 8 ], literature review [ 11 ] and consultative workshop [ 30 ]. In other domains and instances, business data consumers identified 179 data quality dimensions through survey [ 28 ], and a review of electronic medical record literature identified 27 data quality dimensions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assessment of data quality and providing feedback to users are essential activities to generate an impact on TB control and prevention efforts [ 10 ]. National TB control programs of high-burden countries like Pakistan, Kenya, and Ethiopia have mentioned data quality issue as a serious concern implicating performance management negatively [ 11 , 12 ]. However in TB control attempts, strategies for the data quality improvement are adopted elsewhere and have generated better data quality results [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attention to the quality in patient care is important in every setting (17) . Billingsely, et.al (2011) sated that the gap in what is done and what should be done can be closed by providers who implement the principles of quality improvement and have good tools and resources to do so (39) . As regarding support received from the TB facility you are visiting; the patients attending public hospitals experienced lower levels of satisfaction with technical quality of TB care, responsiveness to patient preferences, and patients' understanding of potential problems of TB medicines this is in agreement with Babikako, et.al (2011) (40) .…”
Section: Quality Of Tb Care From the Perspective Of Patientsmentioning
confidence: 99%